2021
DOI: 10.1186/s40168-021-01177-9
|View full text |Cite
|
Sign up to set email alerts
|

Leave no stone unturned: individually adapted xerotolerant Thaumarchaeota sheltered below the boulders of the Atacama Desert hyperarid core

Abstract: Background The hyperarid core of the Atacama Desert is an extremely harsh environment thought to be colonized by only a few heterotrophic bacterial species. Current concepts for understanding this extreme ecosystem are mainly based on the diversity of these few species, yet a substantial area of the Atacama Desert hyperarid topsoil is covered by expansive boulder accumulations, whose underlying microbiomes have not been investigated so far. With the hypothesis that these sheltered soils harbor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 131 publications
(111 reference statements)
1
28
1
Order By: Relevance
“…Nitrosocosmicus, and Ca . Nitrosodeserticola, the three described genera in the family Nitrososphaeraceae (Stieglmeier et al ., 2014; Lehtovirta-Morley et al ., 2016; Hwang et al ., 2021) (Fig. 2a; Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrosocosmicus, and Ca . Nitrosodeserticola, the three described genera in the family Nitrososphaeraceae (Stieglmeier et al ., 2014; Lehtovirta-Morley et al ., 2016; Hwang et al ., 2021) (Fig. 2a; Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Recent AOA comparative population genomics and phylogenomic analyses have shown that V-type ATPase genes were widely distributed among deep-sea water column [11] and sedimentary [76] Nitrosopumilales AOA and desert Nitrososphaerales AOA populations [77]. Apart from the experimentally tested function in low pH adaptation, AOA V-type ATPase may be also coupled to sodium (Na + ) motive force at high pH levels and protect cells from high-salt stress [24, 77]. The ATPase subunit phylogenetic trees show that the AOA V-type ATPase subgroup rooted with Nitrosomirales AOA variants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this scenario, in recent decades, some alternatives have been developed to improve this situation. The use of beneficial bacteria as biotreatments is on the rise, since they are a sustainable and ecologically friendly alternative [ 30 , 31 , 32 ]. Among other mechanisms, these bacteria improve the response to different stresses by protecting the roots (exopolysaccharides and biofilms) and improving their number, length and distribution through the production of auxins, thereby reaching less accessible water sources.…”
Section: Introductionmentioning
confidence: 99%
“…Among other mechanisms, these bacteria improve the response to different stresses by protecting the roots (exopolysaccharides and biofilms) and improving their number, length and distribution through the production of auxins, thereby reaching less accessible water sources. In addition, they are capable of regulating other phytohormones such as ethylene through the production of ACC (1-aminocyclopropane-1-carboxylate) deaminase [ 30 , 33 ]. The action of this enzyme prevents the accumulation of ethylene during periods of drought, thus reducing the loss of leaves and roots, which allows more complex root architecture to be maintained [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation